Bibliometric Analysis Of Islamic Letters Of Credit - Azzahro, Siti Fatimah; Aufa, Aufa; Indra, Indra (JPS (Jurnal Perbankan Syariah), 2024)
Research mapping is essential to describe the topic and appropriate references before conducting research, including Islamic letters of credit. This research aims to review the literature on Islamic letters of credit. This research is a literature review using bibliometric methods with the Dimensions database. The keyword used in the article search is Islamic letter of credit. The data found and processed was 56 articles published from 2010-2023. The data was processed using Microsoft Excel and Bibilioshiny R programs. This research shows that most of the most productive writers come from Malaysia and Turkey. A topic that can be developed for further research is Islamic economic contracts linked to Islamic letters of credit. This research can be used as a reference for future research, as well as information regarding research gaps and an overview of research conditions regarding Islamic letters of credit, which will be developed to be broader and more varied.